CHANGE MANAGEMENT - AN IMPORTANT PART OF TRANSPORT COMPANY MANAGEMENT - Šukalová, Viera (Doprava a spoje, 2012)
The business environment today is characterized by globalization and internationalization. These effects extend to all segments of society constant change. Change is some variation, excitement, irregularity, surprise, something with which to count. Managerial work becomes more challenging in the current period; to the modern equipment of transport company managers belong knowledge of change management.